1997
DOI: 10.1146/annurev.ento.42.1.451
|View full text |Cite
|
Sign up to set email alerts
|

The Biology, Ecology, and Management of the Cat Flea

Abstract: The cat flea, Ctenocephalides felis felis, is the most important ectoparasite of domestic cats and dogs worldwide. In addition to its annoyance to pets and humans, C. felis felis is responsible for flea bite allergy dermatitis and the transmission of dog tapeworm. The abiotic and biotic factors that affect the development of immature stages are reviewed with special emphasis given to those aspects directly affecting control. Factors influencing host selection and feeding by adults are summarized. Recent studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
177
0
9

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(197 citation statements)
references
References 93 publications
3
177
0
9
Order By: Relevance
“…Perhaps seemingly counterintuitive to our finding, we showed that abundance of hostseeking C. felis was significantly lower in homesteads that reported dog ownership. However, this is likely because dogs are a preferred host for C. felis, 49 thus, presence of this host may reduce the abundance of host-seeking fleas inside huts. However, C. felis is an inefficient vector of Y. pestis and is an unlikely bridging vector from zoonotic hosts to humans because of its infrequent feeding on rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps seemingly counterintuitive to our finding, we showed that abundance of hostseeking C. felis was significantly lower in homesteads that reported dog ownership. However, this is likely because dogs are a preferred host for C. felis, 49 thus, presence of this host may reduce the abundance of host-seeking fleas inside huts. However, C. felis is an inefficient vector of Y. pestis and is an unlikely bridging vector from zoonotic hosts to humans because of its infrequent feeding on rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Self-inoculation with flea excrement may result in direct transmission to a flea-infested dog. Dogs and cats are commonly infested with the same flea (Ctenophalides felis) [58] that is known to transmit B. henselae from infected to SPF cats [16]. Both C. felis from cats and dogs and C. canis from dogs were reported to be positive for B. henselae DNA [32].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the narrow host range of the human body louse (43), fleas and ticks can feed on a broad range of mammals (44). Furthermore, lice have a generation time of less than 1 month (45), cat fleas of less than 3 months (46), whereas ticks can have a lifespan of several years (47).…”
Section: Integration Of Megareplicon Sequences Members Of the Genusmentioning
confidence: 99%